Conspiracy Theories in the Time of Covid-19 - Clare Birchall; Peter Knight (Routledge, 2022)
Conspiracy Theories in the Time of Covid-19 provides a wide-ranging analysis of the emergence and development of conspiracy theories during the Covid-19 pandemic, with a focus on the US and the UK.The book combines digital methods analysis of large datasets assembled from social media with politically and culturally contextualised close readings informed by cultural studies. In contrast to other studies which often have an alarmist take on the'infodemic,'it places Covid-19 conspiracy theories in a longer historical perspective. It also argues against the tendency to view conspiracy theories as merely evidence of a fringe or pathological way of thinking. Instead, the starting assumption is that conspiracy theories, including Covid-19 conspiracy theories, often reflect genuine and legitimate concerns, even if their factual claims are wide of the mark. The authors examine the nature and origins of the conspiracy theories that have emerged; the identity and rationale of those drawn to Covid-19 conspiracism; how these conspiracy theories fit within the wider political, economic and technological landscape of the online information environment; and proposed interventions from social media platforms and regulatory agencies.This book will appeal to anyone interested in conspiracy theories, misinformation, culture wars, social media and contemporary society.The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.